Agricultural research for resource-poor farmers part I: transfer-of-technology and farming systems research - Chambers, Robert; Jiggins, Janice (1987)
The greatest challenge now facing agricultural science is not how to increase production overall but how to enable resource-poor farmers to produce more. The transfer-of-technology (TOT) model of agricultural research is part of the normal professionalism of agricultural scientists. In this model, scientists largely determine research priorities, develop technologies in controlled conditions, and then hand them over to agricultural extension to transfer to farmers. Although strong structures and incentives sustain this normal professionalism, many now recognize the challenge of its bad fit with the needs and conditions of hundreds of millions of resource-poor farm (RPF) families. In response to this problem, the TOT model has been adapted and extended through multi-disciplinary farming systems research (FSR) and on-farm trials. These responses retain power in the hands of scientists. Information is obtained from farmers and processed and analysed in order to identify what might be good for them. A missing element is methods to encourage and enable resource-poor farmers themselves to meet and work out what they need and want.